The Coronavirus Will Not Change the long-Term Upward Trend of China’s Economic Development - X. Zhang (Финансы: теория и практика)
The author investigates the impact of COVID‑19 and macro-policy adjustment on China’s economic development. The aim is to describe the situation and trend of China’s economic development before and after COVID‑19. The research method is the comparative data analysis. The study shows that in response to COVID‑19, the Chinese government, on the one hand, has accelerated its opening-up, taken the opportunity of fighting against the pandemic to provide medical assistance to and cooperate with other countries, and actively promoted the building of a community with a shared future for mankind and the process of globalization. On the basis of the Belt and Road Initiative and multilateral, regional, and subregional cooperation mechanisms such as the United Nations, Shanghai Cooperation Organization, BRICS (Brazil, Russia, India, China, South Africa), G20 (Group of 20), and APEC (Asia-Pacific Economic Cooperation), China and the Eurasian Economic Union began to cooperate more frequently and the trade relations between Japan, South Korea, and European developed countries became closer. Meanwhile, committed to building a global interconnection partnership, China actively participates in global economic governance and provides various public products. The Chinese government has proposed “Six Guarantees” on the basis of “Six Stability”. In order to achieve the purpose of stabilizing foreign trade and expanding imports, China has imposed various measures to accelerate the liberalization and facilitation of international trade and investment, such as implementing the new version of the “Foreign Investment Law”, establishing free trade zones, and promoting its experience and organizing international import expositions. Additionally, the Chinese government also implemented targeted fiscal and monetary policies, increased support for enterprises, especially small and medium-sized enterprises, and promoted the construction of “new infrastructure” and innovation of business model, which have formed the driving forces for the transformation of the economic development model in China from traditional business to cloud business, from traditional marketing to live streaming marketing, from traditional sales to online sales. The author concluded thatChina’s adjustment of macro policies in response to COVID‑19 was effective and played an important role in the resumption of production and life, stabilizing foreign trade activities, releasing domestic demand and promoting stable and sustained growth of the economy